2020
DOI: 10.1111/nin.12335
|View full text |Cite
|
Sign up to set email alerts
|

Between health and death: The intense emotional pain experienced by transplant nurses

Abstract: The process of organ donation and transplantation carries a wide range of moral and ethical issues. The transplant co-ordinator (henceforth TC) is expected to be responsible for the course of the procedure that leads to a successful organ procurement. The TC is a key person in the process of obtaining the consent for organs for transplantation from deceased or living donors (Arie, 2008;Matesanz & Dominguez-Gil, 2007;Sikora, Czerwiński, Danek, & Lisik, 2014). Usually, five major ethical dilemmas arise for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Also, OTDCs may face situations where they have responsibilities without authority resulting in a sense of powerlessness that negatively affect their feelings of personal accomplishment. 30 Therefore, personal accomplishment is considered a component of burnout, but the studies that investigated this attribute Open access did not report reduced levels of personal accomplishment among OTDCs according to the Maslach Burnout Inventory subscale scores. 23 25 Job attitudes Job attitudes included OTDC behaviour and expectations related to their role and work.…”
Section: Personal Accomplishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, OTDCs may face situations where they have responsibilities without authority resulting in a sense of powerlessness that negatively affect their feelings of personal accomplishment. 30 Therefore, personal accomplishment is considered a component of burnout, but the studies that investigated this attribute Open access did not report reduced levels of personal accomplishment among OTDCs according to the Maslach Burnout Inventory subscale scores. 23 25 Job attitudes Job attitudes included OTDC behaviour and expectations related to their role and work.…”
Section: Personal Accomplishmentmentioning
confidence: 99%
“…By fulfilling those requests, OTDCs may experience emotional pain and guilt. 30 Additionally, sometimes OTDCs know that the donor is not ideal for donation, but they are still told to go forward with the procedure by management, offering less than optimal organs for transplantation, slowing down the process for staff and the donor's family. 9 30 In unfortunate cases, patients declared brain dead receive less optimal and even precarious treatment by the care team since they do not see the point in continuing treatments, causing ethical and emotional conflicts among OTDCs and the care team.…”
Section: Value Conflictmentioning
confidence: 99%
“…Previous studies revealed that OR nurses expressed feelings of emptiness, helplessness and distress when participating in organ procurement procedures due to the donor's unexpected and tragic death and found it difficult to accept (Anderson, 2005;Wang & Lin, 2009). Similarly, this moral distress is experienced by other health professionals, such as donor coordinators (Tarabeih & Bokek-Cohen, 2020).…”
Section: Organ Procurement Proceduresmentioning
confidence: 99%
“…Parental kidney donation to pediatric end‐stage renal disease (ESRD henceforth) patients represents a promising solution to the problem of the shortage of kidneys available for transplantation. This paucity is a part of a larger phenomenon of the disparity between the number of individuals who need organ transplantation and the pool of available donors (Duivenbode et al, 2020; Padela & Duivenbode, 2018; Tarabeih & Bokek‐Cohen, 2020). Previous studies have shown that it is usually the mothers who agree to donate their kidney to the sick child, while the fathers tend much less to donate (Bal, & Saikia, 2007; Hidalgo et al, 2001; Zeiler, 2009).…”
Section: Introductionmentioning
confidence: 99%